Dynamic cellular complexity of anoxygenic phototrophic sulfur bacteria in the chemocline of meromictic Lake Cadagno - Danza, Francesco (PLoS One, 2017)
The meromictic Lake Cadagno is characterized by a compact chemocline with high concentrations of anoxygenic phototrophic purple sulfur bacteria (PSB) and green sulfur bacteria (GSB). The co-occurrence of phylogenetically distant bacterial groups such as PSB and GSB in the same ecological niche, makes the chemocline of Lake Cadagno an ideal system for studying the conditions and consequences of coexistence of photosynthetic bacteria populations. In this study, we applied flow cytometry (FCM) as a fast tool to identify metabolic changes due to the production and consumption of inclusion bodies such as sulfur globules (SGBs), and follow population dynamics of closely related anoxygenic photosynthetic sulfur bacteria in their natural environment. Large-celled PSB Chromatium okenii and GSB Chlorobium populations were reliably separated and identified due to differences in auto-fluorescence and cell size. Moreover, we showed that these dominant taxa share the same ecological niche over seasonal periods. Taking advantage of FCM detection of dynamic cellular complexity variation during phases of photosynthetic activity, we identified an unexpected alternation in PSB versus GSB metabolic activity, indicating dynamic interspecific interactions between these two populations.